Evolutionary Analysis Points to Divergent Physiological Roles of Type 1 Fimbriae in Salmonella and Escherichia coli - Dagmara I. Kisiela; Sujay Chattopadhyay; Veronika Tchesnokova; Sandip Paul; Scott J. Weissman; Irena Medenica; Steven Clegg; Evgeni V. Sokurenko (mBio, 2013)
ABSTRACT Salmonella and Escherichia coli mannose-binding type 1 fimbriae exhibit highly similar receptor specificities, morphologies, and mechanisms of assembly but are nonorthologous in nature, i.e., not closely related evolutionarily. Their operons differ in chromosomal location, gene arrangement, and regulatory components. In the current study, we performed a comparative genetic and structural analysis of the major structural subunit, FimA, from Salmonella and E. coli and found that FimA pilins undergo diverse evolutionary adaptation in the different species. Whereas the E. coli fimA locus is characterized by high allelic diversity, frequent intragenic recombination, and horizontal movement, Salmonella fimA shows structural diversity that is more than 5-fold lower without strong evidence of gene shuffling or homologous recombination. In contrast to Salmonella FimA, the amino acid substitutions in the E. coli pilin heavily target the protein regions that are predicted to be exposed on the external surface of fimbriae. Altogether, our results suggest that E. coli, but not Salmonella, type 1 fimbriae display a high level of structural diversity consistent with a strong selection for antigenic variation under immune pressure. Thus, type 1 fimbriae in these closely related bacterial species appear to function in distinctly different physiological environments. IMPORTANCE E. coli and Salmonella are enteric bacteria that are closely related from an evolutionary perspective. They are both notorious human pathogens, though with somewhat distinct ecologies and virulence mechanisms. Type 1 fimbriae are rod-shaped surface appendages found in most E. coli and Salmonella isolates. In both species, they mediate bacterial adhesion to mannose receptors on host cells and share essentially the same morphology and assembly mechanisms. Here we show that despite the strong resemblances in function and structure, they are exposed to very different natural selection environments. Sequence analysis indicates that E. coli, but not Salmonella, fimbriae are subjected to strong immune pressure, resulting in a high level of major fimbrial protein gene shuffling and interbacterial transfer. Thus, evolutionary analysis tools can provide evidence of divergent physiological roles of functionally similar traits in different bacterial species.